2011
DOI: 10.1080/17449642.2011.632721
|View full text |Cite
|
Sign up to set email alerts
|

Equality, justice and gender: barriers to the ethical university for women

Abstract: Academic women experience working in higher education differently to their male counterparts. This article argues that the unequal position of women academics is unethical, irrespective of whether one takes a consequentialist or deontological ethical position. By drawing on a range of international studies, the article explores the reasons for this inequity, suggesting that the 'cult of individual responsibility', the positioning of women academics as 'other' and the impact of having a family are significant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Similarly, Grummell, Devine, and Lynch (2009) found that the language interviewees used about balancing childcare and work responsibilities in a study of senior appointments in Ireland was significant. Caring was assumed to be a woman's problem see Aiston (2011) for a fuller discussion of this point).…”
Section: Gender and Research Productivitymentioning
confidence: 99%
“…Similarly, Grummell, Devine, and Lynch (2009) found that the language interviewees used about balancing childcare and work responsibilities in a study of senior appointments in Ireland was significant. Caring was assumed to be a woman's problem see Aiston (2011) for a fuller discussion of this point).…”
Section: Gender and Research Productivitymentioning
confidence: 99%
“…Researchers such as (Aiston, 2011;Ogbugo, 2006) side with the above authors and opine that the scarcity of mentors for female academics and their being quarantined in networking circles has cemented the existing organisational culture in universities. Cognisant to the foregoing, it is clear that there is a need for serious change of mind set such that mentoring of academics also matches strategic goals of a university so mentoring is not understood as an unformulated idea (Shaw, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We need to further unpack and make sense of such experiences that shape a profoundly gendered academia as a workplace lacking equity and diverse representation. Such an unequal position of women academics is inherently unethical in it exacerbates inequity through a 'cult of individual responsibility' that positions women academics in an 'othering' process (Aiston, 2011) that can have deeply traumatic and damaging consequences for women professionally and emotionally. This kind of workplace is a 'psychotic University' (Sievers, 2008), 'unethical' (Aiston, 2011) and inherently 'dehumanising' (Christou, 2016) in viewing 'the Academy as an object of subjugation in the multipolarity of an oppressive logic of neoliberal governance…and liminality of learning' (ibid, 36) when it does not practice the principles of ethics that it purports to advance.…”
Section: Resultsmentioning
confidence: 99%